If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10t + 14 + -3t = 0 Reorder the terms: 14 + 10t + -3t = 0 Combine like terms: 10t + -3t = 7t 14 + 7t = 0 Solving 14 + 7t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 7t = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 7t = 0 + -14 7t = 0 + -14 Combine like terms: 0 + -14 = -14 7t = -14 Divide each side by '7'. t = -2 Simplifying t = -2
| 3x-4=10x-23 | | 4(0)-7y=56 | | 5x+16=13x-72 | | 4x-7(0)=56 | | 7x-10x=36 | | 72-3x=15x+24 | | 3+12x=47+x | | 7y-3x+4y+6x= | | 2(7)+7y=98 | | 10x+8=6x+24 | | 2x+7(0)=98 | | 5e^3x=21 | | 10-9x=58-37x | | 10x-19=71 | | 10x+7=5x-3 | | 2(0)+7y=98 | | 4x+25=12x-63 | | -7+18=39 | | 10x+3=5x-3 | | 7e^2x=27 | | 3z^2-9=0 | | 11x-11=9x+1 | | y=4(4)-2 | | e^2x=1.4 | | -16t^2+64t=0 | | 8r+9=41 | | 9x-16=83 | | x^2-0.6x-2.8=0 | | 6xy-y+2y-4xy= | | g(x)=-(2x+6) | | 2x^2+18x=0 | | 20+c=4c-7 |